2021
DOI: 10.1111/bjhp.12550
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐vaccination subjective norms moderate the relationship between conspiracy mentality and vaccination intentions

Abstract: Objectives. Increasing vaccination hesitancy threatens societies' capacity to contain pandemics and other diseases. One factor that is positively associated with vaccination intentions is a supportive subjective norm (i.e., the perception that close others approve of vaccination). On the downside, there is evidence that negative attitudes toward vaccinations are partly rooted in conspiracy mentality (i.e., the tendency to believe in conspiracies). The objective of this study is to examine the role of subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 43 publications
3
46
0
5
Order By: Relevance
“…Experimental research in which conspiracy theory belief was manipulated has found it reduces participants’ intentions to engage in political and sustainable behaviours [ 20 ], and influences mediators of unethical behaviour [ 80 , 81 ]. Furthermore, anti-vaccination conspiracy theories facilitate vaccine hesitancy [ 82 84 ] especially during the COVID-19 pandemic [ 85 ], and negatively impact vaccination intentions [ 9 , 19 , 72 , 82 , 83 ]. Research into the effect beliefs and risk perceptions have on behaviour within health also allow us to reasonably predict that risk perceptions [ 86 ] and perceptions of severity of risk can predict behaviour [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research in which conspiracy theory belief was manipulated has found it reduces participants’ intentions to engage in political and sustainable behaviours [ 20 ], and influences mediators of unethical behaviour [ 80 , 81 ]. Furthermore, anti-vaccination conspiracy theories facilitate vaccine hesitancy [ 82 84 ] especially during the COVID-19 pandemic [ 85 ], and negatively impact vaccination intentions [ 9 , 19 , 72 , 82 , 83 ]. Research into the effect beliefs and risk perceptions have on behaviour within health also allow us to reasonably predict that risk perceptions [ 86 ] and perceptions of severity of risk can predict behaviour [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the belief in conspiracy theories which affect levels of trust regarding the effectiveness and safety of the COVID-19 vaccines [3,6,13], have remained unchanged throughout the pandemic [8]. Consequently, in the context of the current pandemic, the belief in COVID-19 conspiracy theories is found to decrease institutional trust [6,14], support for government regulations, and the use of preventive measures (i.e., wearing a face mask, maintaining social distance, and frequent handwashing) [15][16][17]. Studies have found that negative attitudes towards experts make people more likely to deny scientific consensus and endorse conspiracies that oppose it [14,[18][19][20].…”
Section: Conspiracy Theoriesmentioning
confidence: 99%
“…However, when people believed there was a strong social norm supporting vaccinations, conspiracy mentality did not predict vaccination intentions. 30 It is important to note that what matters is not the actual behavioural norm, but rather what people perceive to be the behavioural norm; indeed, people often do not accurately perceive the strength of a behavioural norm. 31 32 If many members of a group have conspiratorial beliefs, which cause them to incorrectly believe that certain behaviour is very uncommon in their group (eg, vaccination among US Republicans), then correcting this view may reduce the effects of conspiratorial beliefs on that behaviour.…”
Section: Create and Highlight Social Normsmentioning
confidence: 99%